2017
DOI: 10.2135/cropsci2016.11.0950
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Photoperiod/Thermosensitive Male Sterility in Rice under US Environments

Abstract: Two‐line hybrid rice (Oryza sativa L.) breeding in the United States and China uses photoperiod/thermosensitive genetic male sterility (PTGMS) to produce lines with fertile or sterile pollen, depending on temperature and/or daylength. Although studied in China for >30 yr, genetic analysis of PTGMS in US environments is lacking. We therefore conducted genetic studies of male sterility over 3 yr in five F2 and BC1F2 populations derived from PTGMS line 2008S in Louisiana and Arkansas. Chi‐squared analyses in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…This greatly reduce the time and resources in making hybrid combination and parental seed production. Moreover, it broadens the available choices of restorers that can generate more combinations which in turn increases the probability of finding the best hybrids [4].…”
Section: Discovery Of Genetic Male Sterile Linesmentioning
confidence: 99%
See 3 more Smart Citations
“…This greatly reduce the time and resources in making hybrid combination and parental seed production. Moreover, it broadens the available choices of restorers that can generate more combinations which in turn increases the probability of finding the best hybrids [4].…”
Section: Discovery Of Genetic Male Sterile Linesmentioning
confidence: 99%
“…Studies conducted under US conditions on indica male sterile line 2008S originated from China showed that male sterility is controlled by two or three recessive genes depending on the location and year of planting (Figure 4). When planted in [4].…”
Section: Genetics Of Male Sterilitymentioning
confidence: 99%
See 2 more Smart Citations